Trends in mortality from Alzheimer’s disease and related dementias with hyperlipidemia in the United States from 1999 to 2020—a CDC WONDER database study - Wang, Junwen; Xia, Kaide; Yang, Dianmei; Wu, Jing; Liu, Longfei; Huang, Ying; Shan, Qing; Zhang, Haiwang; Wang, Yiming (Frontiers in Neurology, 2025)
BackgroundThe co-occurrence of Alzheimer’s disease and related dementias (ADRD) with hyperlipidemia represents a growing public health burden amid population aging. Although both conditions have been independently linked to increased morbidity and mortality, national trends in ADRD-related mortality involving hyperlipidemia remain poorly characterized.MethodsWe conducted a retrospective, population-based study using mortality data from the U.S. Centers for Disease Control and Prevention Wide-ranging Online Data for Epidemiologic Research (CDC WONDER) from 1999 to 2020. Deaths with co-listed International Classification of Diseases, Tenth Revision codes for ADRD and hyperlipidemia were identified. Age-standardized mortality rates (ASMR) were calculated per 100,000 persons using the 2000 U.S. standard population. Joinpoint regression was employed to estimate annual percentage change (APC) and average annual percentage change (AAPC) with 95% confidence intervals (CI).ResultsBetween 1999 and 2020, the number of deaths related to ADRD with hyperlipidemia increased from 519 to 21,969, with the ASMR rising from 0.19 to 5.32 per 100,000 (AAPC: 15.25%; 95% CI: 14.37–17.31). A sharp rise in mortality was observed after 2018 across nearly all subgroups. Males had a steeper increase than females (AAPC: 16.31% vs. 14.97%). Non-Hispanic Black individuals had the highest ASMR in 2020 (5.53 per 100,000), while Asian/Pacific Islanders had the most rapid increase (AAPC: 21.80%). Regionally, the South showed the highest burden, while the Northeast exhibited the fastest growth (AAPC: 17.77%). Rural areas had a higher ASMR than metropolitan areas (6.29 vs. 5.09 per 100,000), with comparable upward trends. Notably, individuals aged ≥85 years accounted for over half of all deaths by 2020 and exhibited the highest age-specific mortality rates.ConclusionADRD-related mortality involving hyperlipidemia has significantly risen in the U.S. over two decades, with notable disparities across demographics and geography, underscoring the need for public-health relevance and coordination to be evaluated in future analytic studies targeting cardiometabolic and cognitive health in high-risk populations.